The Influence of Hybrid Work Models on Employee Productivity and Well-Being - Oslan Juliana Simbolon; Thomas H. Sihombing (Cv. Data Sinergi Digital, 2025)
This study examines the impact of hybrid work model implementation on employee productivity and well-being in Indonesian organizations. The hybrid model, combining remote and on-site work, is considered an adaptive post-pandemic strategy with economic and psychological implications. A mixed-methods explanatory sequential design was employed. Quantitative data were collected from 500 employees, measuring productivity through Key Performance Indicators (KPI) extracted from HRIS platforms (SAP SuccessFactors and Workday) and well-being using the WHO-5 Index. Analyses included descriptive statistics, paired t-tests, and linear regression. Complementary qualitative insights were obtained from 30 structured interviews and analyzed thematically. Results show that average KPI scores increased significantly from 77.38 to 81.32 (p < 0.001; Cohen’s d = 1.06), while WHO-5 scores rose from 55.03 to 63.76 (p < 0.001; Cohen’s d = 1.32). However, regression analysis revealed that improved well-being was not directly associated with productivity gains (p = 0.788). Thematic analysis identified four central themes: flexibility and time efficiency, enhanced work-life balance, collaboration challenges, and risks of digital fatigue. The study concludes that hybrid work substantially enhances both productivity and well-being, though their relationship is not linear. Organizational factors, particularly communication, managerial support, and digital workload management are critical for success. These findings contribute to human resource management literature and highlight the strategic significance of hybrid work in sustaining corporate performance in uncertain environments.